2013
DOI: 10.1037/a0032507
|View full text |Cite
|
Sign up to set email alerts
|

Managing work, family, and school roles: Disengagement strategies can help and hinder.

Abstract: The extent to which individuals manage multiple role domains has yet to be fully understood. We advance past research by examining the effect of interrole conflict among three very common and critically important life roles-work, family, and school-on three corresponding types of satisfaction. Further, we examine individual-based techniques that can empower people to manage multiple roles. In doing so, we integrate the disengagement strategies from the work recovery and coping literatures. These strategies foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…Finally, the use of avoidance coping may not allow individuals to anticipate or proactively monitor possible time conflict between different life domains. As past research has suggested that this coping style is more likely to impact conflict than enrichment (Cheng & McCarthy, ; see also Carver & Scheier, ), we do not expect a direct effect of avoidance coping on work–family enrichment. These arguments, in combination with the proposed negative relationships between GMA/conscientiousness and avoidance coping, lead us to predict: Hypothesis 7 :(a) GMA/(b) conscientiousness has a negative indirect effect on work–family conflict mediated through avoidance coping styles. …”
Section: Hypothesis Developmentmentioning
confidence: 62%
See 2 more Smart Citations
“…Finally, the use of avoidance coping may not allow individuals to anticipate or proactively monitor possible time conflict between different life domains. As past research has suggested that this coping style is more likely to impact conflict than enrichment (Cheng & McCarthy, ; see also Carver & Scheier, ), we do not expect a direct effect of avoidance coping on work–family enrichment. These arguments, in combination with the proposed negative relationships between GMA/conscientiousness and avoidance coping, lead us to predict: Hypothesis 7 :(a) GMA/(b) conscientiousness has a negative indirect effect on work–family conflict mediated through avoidance coping styles. …”
Section: Hypothesis Developmentmentioning
confidence: 62%
“…We propose that individuals who are high on GMA and conscientiousness are more likely to use problem coping and eschew the use of ineffective coping styles such as avoidance coping (Connor‐Smith & Flachsbart, ). Based on the differential salience perspective, the use of problem coping may allow individuals to better manage demands and optimize resource utilization, resulting in less conflict and more enrichment (Cheng & McCarthy, ; Folkman & Moskowitz, ). In contrast, the use of avoidance coping may leave stressors unresolved thereby allowing them to spill over across domains and increase work–family conflict.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…WFC was measured using four of the items in the five‐item scale developed by Netemeyer, Boles, and McMurrian (). Sample items include the following: “The demands of my work interfere with my home and personal/family life” and “My job produces strain that makes it difficult to fulfill personal/family duties.” Due to concerns about survey length and consistent with previous research (e.g., Cheng & McCarthy, ), we removed one item from the survey: “Things I want to do at home do not get done because of the demands my job puts on me.” The scale was administered on a 5‐point Likert scale (1 = strongly disagree to 5 = strongly agree ). The average reliability of the scale across countries was calculated as 0.88, which ranged between 0.73 (Korea) and 0.93 (Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Disengagement strategies include cognitive avoidance, psychological detachment, and cognitive distortion [46].…”
Section: Accepted Manuscriptmentioning
confidence: 99%